Evaluating The Effectiveness of Total Productive Maintenance (TPM) Program in Texas Instruments Malaysia - Lim, Cheng Hoe (1998)
Today, the economic environment surrounding corporations becomes severe, and total elimination of waste is required for the survival of the corporation. Therefore, wastes generated due to the failure shutdown of facilities that have been built with huge investment and wastes such as defective products should be absolutely eliminated. Requirements for product quality become stringent, and not even one defective product would be allowed. Quality assured delivery of total quantity is now taken for granted. Thus in order for organization to remain competitive, reduce production cost, and meeting stringent product quality requirements, Total Productive Maintenance (rPM) was introduced and has been recognized as necessary for organization survival. The purpose of this research is to determine the effectiveness of the TPM program in TIM. Specifically, this study aimed: • To understand the TPM program. • To determine the effectiveness of TPM in achieving the organization operation productivity, operation cost and product quality. • To determine the constraints and issues during TPM fan-out plant wide in TIM. • To discuss the managerial implications of the results. • To provide information regarding the implementation of TPM program that may be useful to other research purposes regarding implementing TPM program. Based on this study, it can be concluded that, TIM has achieved the objectives through the implementation of TPM program. With better equipment performance and productivity, the cost of operation and costs per unit in TIM could be reduced. With the lower cost of operation, this will improved the ability for TIM to compete in the industry. The implementation of TPM program in TIM helped TIM achieved a lot of tangible and intangible benefits, where this benefits increased the organization image and status in the industry.